2007
DOI: 10.1373/clinchem.2007.086272
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Hyperhomocysteinemia Reduces Bone Quality in Rats

Abstract: Results: Compared with controls, 3 months of moderate or intermediate HHCY increased mean (SD) bone fragility at the femoral neck by 18% (6%) in methionine-fed (P ‫؍‬ 0.001) and 36% (13%) in homocystine-fed rats (P <0.001). Mean (SD) BAr/TAr at the distal femur in methionine and homocystine groups was decreased by 45% (21%; P ‫؍‬ 0.001) and 93% (9%; P ‫؍‬ 0.001), respectively. At the femoral neck, BAr/TAr was decreased by 19% (11%; P <0.001) and 55% (19%; P <0.001). At the lumbar spine, the reduction of BAr/TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…32 Another rat study showed that increased homocysteinemia induced by a diet enriched in methiononine or homocysteine -which is likely to interfere with crosslink formation -for 3 months resulted in decreased bone formation, bone volume and bone strength at the distal femur. 33 The impact of an increase of enzymatic crosslinks on bone strength can also be investigated using fetal bovine cortical bone, which is characterized by a low level of these molecules. By incubating bone samples at 37 ° C for 60 days, we showed that the increase in PYD and DPD was positively associated with an increase of ultimate stress and post-yield energy absorption.…”
Section: Collagen Post-translational Modifications and Bone Strengthmentioning
confidence: 99%
“…32 Another rat study showed that increased homocysteinemia induced by a diet enriched in methiononine or homocysteine -which is likely to interfere with crosslink formation -for 3 months resulted in decreased bone formation, bone volume and bone strength at the distal femur. 33 The impact of an increase of enzymatic crosslinks on bone strength can also be investigated using fetal bovine cortical bone, which is characterized by a low level of these molecules. By incubating bone samples at 37 ° C for 60 days, we showed that the increase in PYD and DPD was positively associated with an increase of ultimate stress and post-yield energy absorption.…”
Section: Collagen Post-translational Modifications and Bone Strengthmentioning
confidence: 99%
“…Hcy is the final degradation product of the methionine pathway and is increased if vitamin B12, folate and/or B6, important co-enzymes of the Hcy degrading re-methylation and trans-sulfuration pathway, are deficient (7). In vivo and in vitro studies suggest that there are direct effects of Hcy and vitamin B12 on bone metabolism (8)(9)(10). In rats, 3 and 5 months of continuous hyperhomocysteinemia causes bone loss and a reduction in bone strength (9).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies suggest that there are direct effects of Hcy and vitamin B12 on bone metabolism (8)(9)(10). In rats, 3 and 5 months of continuous hyperhomocysteinemia causes bone loss and a reduction in bone strength (9). Cell culture experiments using human osteoclasts and osteoblasts revealed a distinct increase in osteoclast activity in the presence of high tHcy and low vitamin B12, B6, and folate concentrations in the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…First experimental evidence for an osteoporotic potency of chronic hyperhomocysteinemia (HHCY) comes from two recent animal studies. (7,8) After 3 and 5 mo of HHCY, healthy adult rats exhibited a distinct loss of cancellous bone and a reduction in bone strength. The adverse effects of HHCY on bone were accompanied by a bonespecific accumulation of HCY, S-adenosyl-homocysteine (SAH), and S-adenosyl-methionine (SAM).…”
Section: Introductionmentioning
confidence: 99%